2003
DOI: 10.1067/mtc.2003.13
|View full text |Cite
|
Sign up to set email alerts
|

Tissue oxygen tension during regional low-flow perfusion in neonates

Abstract: In a piglet model, regional low-flow perfusion at 20 mL/(kg x min) resulted in lower cortical tissue oxygenation but better recovery than did perfusion at 40 mL/(kg x min). Neither flow rate adequately oxygenated organs in the lower torso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
0
26
2
Order By: Relevance
“…In contrast, SCP at 20 mL ⅐ kg Ϫ1 ⅐ min Ϫ1 resulted in a lesser cortical Po 2 and a relatively greater proportion of hypoxic tissue but, overall, recovery was better. However, Andropoulos et al 5 demonstrated that, in contrast to our results and those by Pigula et al 3 and DeCampli et al, 17 a mean SCP-flow at 63 mL ⅐ kg Ϫ1 ⅐ min Ϫ1 was required to maintain cerebral oxygen saturation and blood flow velocity within Ϯ10% of full flow CPB values during SCP for neonatal aortic arch reconstruction. This is more sophisticated, since Andropoulos and coworkers used pH-stat acid-base management, compared with ␣-stat used in our study and by both Pigula 3 and DeCampli.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, SCP at 20 mL ⅐ kg Ϫ1 ⅐ min Ϫ1 resulted in a lesser cortical Po 2 and a relatively greater proportion of hypoxic tissue but, overall, recovery was better. However, Andropoulos et al 5 demonstrated that, in contrast to our results and those by Pigula et al 3 and DeCampli et al, 17 a mean SCP-flow at 63 mL ⅐ kg Ϫ1 ⅐ min Ϫ1 was required to maintain cerebral oxygen saturation and blood flow velocity within Ϯ10% of full flow CPB values during SCP for neonatal aortic arch reconstruction. This is more sophisticated, since Andropoulos and coworkers used pH-stat acid-base management, compared with ␣-stat used in our study and by both Pigula 3 and DeCampli.…”
Section: Discussioncontrasting
confidence: 77%
“…This flow rate maintained brain capillary oxygen saturation at 50-70%, and reduced apoptotic cell death seven fold compared to DHCA, although only to a level slightly above control sham operated animals. de Campli et al (22) studied neonatal piglets with an ACP model at 20 vs. 40 ml/kg/min, and determined that the higher ACP flow rates maintained cortical oxygen tension at pre-CPB levels, whereas the lower flow rate did not.…”
Section: Review Of Acp Publicationsmentioning
confidence: 99%
“…Table 3 depicts the median regional histologic scores, NDS and OPC on POD 1. The median THS was 9 (range 0-11) for the FF group, 12 (range [4][5][6][7][8][9][10][11][12][13][14] for the HCA group and 9 (range 0-11) for the SCP group ( p = NS). Histopathologic changes were found in all groups.…”
Section: Scorementioning
confidence: 92%
“…DeCampli et al reported that 50% of piglets undergoing SCP with a flow rate of 40 ml kg À1 min À1 had significant upper torso oedema, metabolic acidosis, and an unstable recovery period, but that none of piglets perfused with 20 ml kg À1 min À1 had such complications [4] suggesting a deleterious effect of increased flow. In contrast to our study, they used an alpha-stat strategy in which there is relatively less cerebral vasodilation (compared with pH-stat strategy).…”
Section: Flow Rate During Scpmentioning
confidence: 96%
See 1 more Smart Citation